Assessing the whole-body protein synthetic response to feeding in vivo in human subjects - Trommelen, Jorn; van Loon, Luc J. C. (Proceedings of the Nutrition Society, 2021)
All tissues are in a constant state of turnover, with a tightly controlled regulation of protein synthesis and breakdown rates. Due to the relative ease of sampling skeletal muscle tissue, basal muscle protein synthesis rates and the protein synthetic responses to various anabolic stimuli have been well defined in human subjects. In contrast, only limited data are available on tissue protein synthesis rates in other organs. Several organs such as the brain, liver and pancreas, show substantially higher (basal) protein synthesis rates when compared to skeletal muscle tissue. Such data suggest that these tissues may also possess a high level of plasticity. It remains to be determined whether protein synthesis rates in these tissues can be modulated by external stimuli. Whole-body protein synthesis rates are highly responsive to protein intake. As the contribution of muscle protein synthesis rates to whole-body protein synthesis rates is relatively small considering the large amount of muscle mass, this suggests that other organ tissues may also be responsive to (protein) feeding. Whole-body protein synthesis rates in the fasted or fed state can be quantified by measuring plasma amino acid kinetics, although this requires the production of intrinsically labelled protein. Protein intake requirements to maximise whole-body protein synthesis may also be determined by the indicator amino acid oxidation technique, but the technique does not allow the assessment of actual protein synthesis and breakdown rates. Both approaches have several other methodological and inferential limitations that will be discussed in detail in this paper.